Museum of Contemporary Art and Planning Exhibition. Shenzhen, China (2007-2016) - Wolf D. Prix (Oz, 2016)
The Museum of Contemporary Art and Planning Exhibition (MOCAPE) is part of the master plan for the Futian Cultural District, the new urban center of Shenzhen. The project combines two independent yet structurally unified institutions: The Museum of Contemporary Art (MOCA) and the Planning Exhibition(PE) as a cultural meeting point and a venue for architectural exhibitions. The lobby, multifunctional exhibition halls, auditorium, conference rooms and service areas will be used jointly.